THE EFFECT OF PSYCHOSOCIAL FACTORS ON ISLAMIC FINANCIAL LITERACY: STRUCTURAL EQUATION MODELLING-PARTIAL LEAST SQUARE (SEM-PLS) APPROACH - Andi Triyawan; Fina Salsabila (Journal of Islamic Economics and Philanthropy, 2021)
has the potential and opportunity to become the world’s Islamic financial center. But, the financial sector of Indonesia is still dominated by conventional finance. The existence of a very wide gap between conventional finance and Islamic finance, charge for Indonesian society to get a high level of Islamic financial literacy. One of the factors that affect the level of Islamic financial literacy is psychosocial factors. This research aims to analyze the direct effect of hopelessness, religiosity, and financial satisfaction factors on Islamic financial literacy and the indirect effect of religiosity on Islamic financial literacy through the hopelessness and financial satisfaction of traders in the Shubuh Market, Dusun Dadung, Sambirejo Village, Mantingan District. This research is quantitative research. The population in this research were 37 traders. The sampling technique used purposive sampling with the number of selected samples is 30 traders. This research uses Structural Equation Modelling (SEM) analysis technique with Partial Least Square (PLS) method by smartPLS 3.0. The result of this research showed that the Islamic financial literacy rate of Shubuh market traders is high with a percentage of 87.25%, financial satisfaction has a positive effect significantly on Islamic financial literacy, hopelessness has a negative effect significantly on Islamic financial literacy, religiosity has a positive effect significantly on financial satisfaction, religiosity has a negative effect significantly on hopelessness, religiosity does no effect or insignificantly on Islamic financial literacy, but religiosity has a positive effect significantly on Islamic financial literacy through the financial satisfaction and hopelessness.